Kebijakan Pemerintah Daerah dalam Penanganan dan Perlindungan Anak yang Berhadapan dengan Hukum di Halmahera Utara - Sukitman Asgar; Sahrestia Kartianti (Wajah Hukum, 2021)
The phenomenon of child violence in North Halmahera Regency continues to increase every year and even the comparison is very significant. So the need for the seriousness of the local government to prevent an increase in cases experienced by children as early as possible through a series of efforts and actions both in the form of socialization and other strategic steps, non-optimal service to children who are in conflict with the law can also affect the development of children especially on the aspects of psychological recovery and children's health. To obtain perfect research results, accurate and supportive data and information are needed. Thus, this research is conducted through a Qualitative Approach which is analyzed juridically and sociologically based on statutory provisions and directly involved in observing the effectiveness of law implementation carried out by local government agencies. After being analyzed through the available approach and data, there are several things that have not been carried out properly. This means that all efforts and policies made by local governments in the field of child protection, especially those dealing with the law, have not met the expectations mandated by the laws and regulations. Where there are several cases of child abuse, they have to break up in the middle of the road due to various considerations, as well as the need for a legal product similar to regional regulations to accommodate and fulfill all the interests and rights of children.